Establishment of a non-integrated iPSC (SDQLCHi068-A) line derived from a patient with autosomal dominant immunodeficiency-14A carrying a heterozygous mutation (c.3061G>A) in PIK3CD gene - Hongmei Xin; Yuqiang Lv; Xuxia Wei; Wei Song; Zilong Li; Yi Liu; Zhongtao Gai (Stem Cell Research, 2024)
Phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit delta (PIK3CD) gene (OMIM#602839) encodes the p110δ catalytic subunit, mainly expressed in immune cells, and is associated with autosomal dominant immunodeficiency-14A with lymphoproliferation (IMD14A, #615513). We generated a human iPS cell line from a 50-month-old boy with IMD14A carrying a heterozygous mutation (c.3061G>A, p.E1021K) in PIK3CD gene. This cell line retains the original mutation site and shows differentiation potential towards three germ layers in vitro, which can be used as a disease model for research.